The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/anie.200705613
|View full text |Cite
|
Sign up to set email alerts
|

PdII‐Catalyzed Monoselective ortho Halogenation of CH Bonds Assisted by Counter Cations: A Complementary Method to Directed ortho Lithiation

Abstract: When the counterion counts: The yield and selectivity of the title transformation of benzoic acid derivatives were improved greatly by using tetraalkyl ammonium salts as additives (see scheme; monoselectivity: 5:1–18:1). These effects are attributed to the influence of counter cations. The halogenated products are versatile intermediates for the construction of substituted aromatic compounds. DMF=N,N‐dimethylformamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(124 citation statements)
references
References 67 publications
3
118
0
3
Order By: Relevance
“…Following ligand-promoted C–H olefination, Pd/C-mediated hydrogenation, and tert -butyl ester deprotection, free acid 239 was obtained in 66% yield over the three steps. Next, we found that 239 could undergo directed ortho -C–H iodination 82 to give differentially functionalized 1,2,4,5-tetrasubstituted arene 240 in 67% yield following conversion to the methyl ester to simplify purification.…”
Section: Identification Of Ligand Scaffolds For Pd(ii)-catalyzed Cmentioning
confidence: 99%
“…Following ligand-promoted C–H olefination, Pd/C-mediated hydrogenation, and tert -butyl ester deprotection, free acid 239 was obtained in 66% yield over the three steps. Next, we found that 239 could undergo directed ortho -C–H iodination 82 to give differentially functionalized 1,2,4,5-tetrasubstituted arene 240 in 67% yield following conversion to the methyl ester to simplify purification.…”
Section: Identification Of Ligand Scaffolds For Pd(ii)-catalyzed Cmentioning
confidence: 99%
“…[1,[4][5][6][7][8] With respect to Pd catalysis, Yu and co-workers have pioneered the use of carboxylate groups as effective promoters of Pd-catalyzed selective CÀH functionalization, [5] which has led to seminal developments in cross-coupling with arylorganometallic reagents; [5a,b, 6] further developments have led to carbonylation, [5c] alkylation, [5d] olefination, [5e,f] oxygenation, [5g] and iodination [5h,i] reactions. Related to this, other carbonyl-based directing groups such as amide derivatives, [7] ketones, [8] and oximes [9] have also resulted in developments in catalytic CÀH bond functionalization.…”
mentioning
confidence: 99%
“…Other solvents, such as DMF, DMSO, dioxane, THF, EtOH and EtOAc were ineffective(Entries 12-16 and 19, Table 1). Our previous studies have shown that acyl hypobromite(BrOAc) generated in situ from carboxylic acid and NBS was more active than NBS(Scheme 2) [32,36] . Accordingly, the effect of carboxylic acids on the bromination was investigated in this paper and the result is consistent with that of the early report [32] .…”
Section: Scheme 1 Synthesis Of Compound 1bmentioning
confidence: 99%